Pengaruh Customer Experience dan Variasi Produk Terhadap Keputusan Pembelian (Studi pada Pelanggan Dea Bakery Kota Blitar) - Kolondam, Melvi Aura Fitra (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
In the current era, the business landscape, particularly within the culinary industry, is experiencing rapid growth. Bakery entrepreneurs are also competing to showcase innovations in the hope of attracting customers to their products, as is the case at Dea Bakery. This study uses a quantitative approach. The research was conducted in Blitar City, East Java. The sampling technique used is non-probability sampling. The sample is 80 respondents using the Ferdinand formula, the sample technique uses purposive sampling, for the reason that by using this technique the researcher can determine certain criteria set. The intended criteria are: (a) Respondents are willing to fill out the questionnaire, (b) Respondents are at least 17 years old, (c) Respondents have made purchases at least twice at the Dea Bakery outlet in Blitar City, (d) Respondents know more than one Dea Bakery product. The data analysis technique used is multiple linear regression analysis. The test results show a significance value of 0.406, which is bigger than 0.05, indicating that customer experience has no partial effect on purchasing decisions. The regression coefficient of 0.571, with a positive direction, and a significance value of 0.001, which is less than 0.05, indicates that product variety has a partial effect on purchasing decisions. The Adjusted R Square value is 0.412, indicating that the independent variables, customer experience, and product variety, simultaneously influence the dependent variable, purchasing decisions. Based on the results of this study, Dea Bakery Kota Blitar is expected to provide seating so that customers do not just come and go after getting their needs, in addition, Dea Bakery Kota Blitar is also expected to expand the reach of advertising in introducing new products.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: customer experience; product variation; purchase decision